The effect of real earnings management, fraud, and earnings informativeness, as the moderating variable, on investment efficiency - Giovani Priscilia; Estralita Trisnawati (Journal of Accounting and Investment, 2023)
Research aims: This study aims to analyze the relationship between real earnings management, fraud, and earnings informativeness, as the moderating variable, on investment efficiency.Design/Methodology/Approach: The samples tested consisted of 333 observations in manufacturing companies during 2018-2020. The hypothesis testing used moderated regression analysis through Eviews-12.Research findings: The results uncovered that real earnings management with cash flow (EM_CFO), production (EM_PROD), and discretionary costs (EM_DISEXP) had a negative effect on investment efficiency, while fraud had a positive effect. Besides, earnings informativeness as the moderation variable only affected fraud on the investment efficiency. Theoretical contribution/Originality: This study used real earnings management with EM_CFO, EM_PROD, and EM_DISEXP as a transition approach from accrual earnings management. In previous studies, fraud was not directly examined on investment efficiency. Adding earnings informativeness as a moderation variable thus gives another perspective on the relationship between independent and dependent variables.Practitioner/Policy implication: The implication for the practitioner is to provide consideration for earnings management, fraud, earnings informativeness, and investment efficiency. From a policy’s view, this study can give an overview to Financial Services Authority (“OJK”) and Investment Coordinating Board (“BKPM”) to consider and know the important elements in the financial statements and encourage investment efficiency.Research limitation/Implication: The limitation is that the coverage of samples was only from the manufacturing industry. Exploring other sectors, extending the period, and deepening analysis is open for better research, including using other proxies in each variable. The implication is not only as additional literature but also can give the shareholders and management an overview of the investment’s decision-making.